Conditional Demand and Endogeneity? A Case Study of Demand for Juice Products - Mark G. Brown; Robert M. Behr; Jonq-Ying Lee (Journal of Agricultural and Resource Economics, 1994)
The question of endogeneity of conditional expenditures, as well as prices, in conditional demand equations for justices is examined. Both conditional expenditures and prices were found to be uncorrelated with the conditional demand errors, based on Wu-Hausman tests. Conditional demand error variance/covariance estimates and corresponding Slutsky coefficient estimates were approximately proportional, as predicted by the theory of rational random behavior, further supporting independence of conditional expenditures and conditional errors for juice demands.